Question
upstudy study bank question image url

11) Show that \( \sin (\theta+x)+\sin (\theta-x)=2 \sin \theta \cos x \) (2) Hence show that \( \sin 43^{\circ}+\sin 17^{\circ}=\cos 13^{\circ} \).

Ask by Wright Malone. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

sin(θ + x) + sin(θ − x) = 2 sin θ cos x Therefore, sin 43° + sin 17° = cos 13°

Solution

1) To prove the identity sin(θ + x) + sin(θ − x) = 2 sin θ cos x, we first expand each sine term using the sine addition and subtraction formulas:   sin(θ + x) = sin θ cos x + cos θ sin x   sin(θ − x) = sin θ cos x − cos θ sin x Now, adding these two expressions:   sin(θ + x) + sin(θ − x)     = (sin θ cos x + cos θ sin x) + (sin θ cos x − cos θ sin x)     = (sin θ cos x + sin θ cos x) + (cos θ sin x − cos θ sin x)     = 2 sin θ cos x Thus, we have proven the identity. 2) To show that sin 43° + sin 17° = cos 13°, notice that the identity from part (1) suggests writing the two sines in the form sin(θ + x) and sin(θ − x). We set up the following:   θ + x = 43°  and  θ − x = 17° Adding these equations gives:   (θ + x) + (θ − x) = 43° + 17°   2θ = 60°   θ = 30° Then, subtracting the equations gives:   (θ + x) - (θ − x) = 43° - 17°   2x = 26°   x = 13° Now, substituting θ = 30° and x = 13° into the identity, we have:   sin 43° + sin 17° = 2 sin 30° cos 13° Since sin 30° = 1/2, it follows that:   2 sin 30° cos 13° = 2 × (1/2) × cos 13° = cos 13° Thus, we have shown that sin 43° + sin 17° = cos 13°.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To show that \( \sin (\theta+x)+\sin (\theta-x)=2 \sin \theta \cos x \), we can use the sine addition and subtraction formulas: \[ \sin(\theta+x) = \sin \theta \cos x + \cos \theta \sin x \] \[ \sin(\theta-x) = \sin \theta \cos x - \cos \theta \sin x \] Adding these two equations: \[ \sin(\theta+x) + \sin(\theta-x) = (\sin \theta \cos x + \cos \theta \sin x) + (\sin \theta \cos x - \cos \theta \sin x) \] \[ = 2 \sin \theta \cos x \] Hence, the first part is proven. Now, for the second part, we start with the expression we need to prove: \[ \sin 43^{\circ} + \sin 17^{\circ} \] Using our earlier result, we can represent this as \( \sin(\theta+x) + \sin(\theta-x) \) where we take \( \theta = 30^{\circ} \) and \( x = 13^{\circ} \): This forms: \[ \sin(30^{\circ} + 13^{\circ}) + \sin(30^{\circ} - 13^{\circ}) = \sin 43^{\circ} + \sin 17^{\circ} \] which by our earlier result is equal to: \[ 2 \sin 30^{\circ} \cos 13^{\circ} = 2 \cdot \frac{1}{2} \cdot \cos 13^{\circ} = \cos 13^{\circ} \] Thus, we have \( \sin 43^{\circ} + \sin 17^{\circ} = \cos 13^{\circ} \), confirming the statement.

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy